Highly selective and dual responsive test paper sensor of Hg2+/ Cr3+ for naked eye detection in neutral water - Das, Priyadip; Ghosh, Amrita; Bhatt, Hitesh; Das, Amitava (RSC Advances, 2012)
A highly selective and sensitive colorimetric and fluorogenic sensor (L1) for Hg2+/Cr3+ is reported. This reagent (L1) was synthesized by reacting 4-((4 (dimethylamino)phenyl)diazenyl)benzene-1-sulfonyl chloride, which has a dimethylaminophenyldiazenyl fragment as a photoactive signalling unit, with 2,2′-(3,3′-azanediylbis(propane-3,1-diyl))diisoindoline-1,3-dione as the receptor fragment. The reagent was characterized by standard analytical and spectroscopic techniques. Electronic spectral studies revealed that the reagent was selective for Hg2+ and Cr3+ in the presence of all other metal ions of Group 1A, IIA and all other common transition metal ions. On binding of L1 to the Hg2+ or Cr3+ centres, a new intense absorption band with a λmax of 509 nm appeared with associated changes in the visually detectable solution colour from yellow to red. Fluorescence spectral studies revealed a significant enhancement in the emission intensities upon coordination to Hg2+ or Cr3+ without any change in the emission wavelength. This could be explained by the efficient interruption of the photo induced electron transfer signalling mechanism involving an unshared pair of electrons from the central tertiary amine centre. An easy to prepare paper test kit, which was obtained by soaking the filter paper in a dichloromethane solution of L1, presents an approach that could be successfully used in the detection of Hg2+ or Cr3+ ions present in neutral aqueous media. This indicates the potential application of this dip strip type sensor for the detection of Hg2+ and Cr3+ in neutral aqueous environments without any spectroscopic instrumentation. Importantly, this reagent binds specifically to Cr3+ in the presence of an excess of iodide ions, which act as a masking agent for Hg2+. To the best of our knowledge, there are very few examples of detection limits lower than the present test strip for Hg2+ in the literature, while, for Cr3+, no such report is available.

Hydrogen bonding interaction between active methylene hydrogen atoms and an anion as a binding motif for anion recognition: experimental studies and theoretical rationalization - Agarwalla, Hridesh; Jana, Kalyanashis; Maity, Arunava; Kesharwani, Manoj K.; Ganguly, Bishwajit; Das, Amitava (Journal of Physical Chemistry A, 2014)
Two new reagents, having similar spatial arrangements for hydrogen atoms of the active methylene functionalities, were synthesized and interactions of such reagents with different anionic analytes were studied using electronic spectroscopy as well as by using 1H and 31P NMR spectroscopic methods. Experimental studies revealed that these two reagents showed preference for binding to F– and OAc–. Detailed theoretical studies along with the above-mentioned spectroscopic studies were carried out to understand the contribution of the positively charged phosphonium ion, along with methylene functionality, in achieving the observed preference of these two receptors for binding to F– and OAc–. Observed differences in the binding affinities of these two reagents toward fluoride and acetate ions also reflected the role of acidity of such methylene hydrogen atoms in controlling the efficiencies of the hydrogen bonding in anion–Hmethylene interactions. Hydrogen bonding interactions at lower concentrations of these two anionic analytes and deprotonation equilibrium at higher concentration were observed with associated electronic spectral changes as well as visually detectable change in solution color, an observation that is generally common for other strong hydrogen bond donor functionalities like urea and thiourea. DFT calculations performed with the M06/6-31+G**//M05-2X/6-31G* level of theory showed that F– binds more strongly than OAc– with the reagent molecules. The deprotonation of methylene hydrogen atom of receptors with F– ion was observed computationally. The metal complex as reagent showed even stronger binding energies with these analytes, which corroborated the experimental results.

Hydrogen bond and ligand dissociation dynamics in fluoride sensing of Re(I)-polypyridyl complex - Verma, Sandeep; Aute, Sunil; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry B, 2015)
Hydrogen bonding interaction plays an essential role in the early phases of molecular recognition and colorimetric sensing of various anions in aprotic media. In this work, the host-guest interaction between fac-[Re(CO)(3)Cl(L)] with L = 4-([2,2'-bipyridin]-4-yl)phenol and fluoride ions is investigated for the hydrogen bond dynamics and the changing local coordination environment. The stoichiometric studies using H-1 NMR and ESI-MS spectroscopies have shown that proton transfer in the H-bonded phenol-fluoride complex activates the dissociation of the CO ligand in the Re(I) center. The phenol-to-phenolate conversion during formation of HF2- ion induces nucleophilic lability of the CO ligand which is probed by intraligand charge transfer (ILCT) and ligand-to-metal charge transfer (LMCT) transitions in transient absorption spectroscopy. After photoexcitation, phenol-phenoxide conversion rapidly equilibrates in 280 fs time scale and the ensuing excited state [ReII(bpy(center dot-)-phenolate(-))(CO)(3)Cl]* undergoes CO dissociation in the ultrafast time scale of similar to 3 ps. A concerted mechanism of hydrogen cleavage and coordination change is established in anion sensing studies of the rhenium complex.

Hydrogen bond assisted photoinduced intramolecular electron transfer and proton coupled electron transfer in an ultrafast time domain using a ruthenium-anthraquinone dyad - Dey, Ananta; Dana, Jayanta; Aute, Sunil; Das, Amitava; Ghosh, Hirendra N. (Photochemical & Photobiological Sciences, 2019)
Quinones play a significant role as primary electron acceptors in the natural photosynthetic system of photosystem II, and their reduction is known to be facilitated by hydrogen-bond donors or protonation. In this study, a ruthenium(ii) polypyridyl complex 1 coupled to an anthraquinone (AQ) functionality through a rigid imidazole (Im) spacer has been synthesized to examine the effect of H-bonding on both the thermal and photoinduced electron transfer reactions. The anthraquinone moiety of complex 1 is fused to a benzi-imidazole system bearing C & xe001;(OMIDLINE)-M-AQ HORIZONTAL ELLIPSISHNIm based H-bonding at one side of the anthraquinone moiety so that intramolecular hydrogen bonding from the imidazole group to the nearby quinone carbonyl can occur. The hydrogen bond formation involving the semiquinone radical anion produced through the photoinduced reduction process in Ru-im-AQ and the imidazole proton in complex 1 resulted in a significant positive shift of one electron reduction potential of complex 1. The kinetics for the formation of the charge-separated states was explored by using femtosecond transient absorption spectroscopy. Hydrogen bonding between water and the reduced anthraquinone accounted for thermodynamic and kinetic stabilization of these charge-separated states. An attempt has been made to assess the relative importance of the driving force and solvent polarity, in the rates of photoinduced electron transfer in complex 1. The 490 nm transient absorption band of anthraquinone radical anions (AQ(-)) and a broad absorption in the 580-750 nm region having maxima at similar to 690 nm have been observed and this is attributed to the generation of a transient Ru3+-species of the corresponding complex 1. Addition of water entails an acceleration of electron transfer rates by a factor of 3.33. The system investigated may serve as a model for the mechanistic diversity of PCET reactions in general with water as a primary proton donor. Furthermore, our studies are relevant for understanding proton-coupled electron transfer (PCET) reactivity of electronically excited states at a fundamental level because changes in hydrogen-bonding strength accompanying changes in redox states may be regarded as a variant form of PCET.